: Deconstruyendo el género en la era digital: explorando nuevas formas de expresión y construcción identitaria. - Zúñiga Maldonado, José Miguel (2025)
This research paper analyzes how digital platforms are transforming the expression and construction of gender identity. It examines the new forms of gender deconstruction through social networks, the challenges faced by diverse gender identities online, and how these interactions are redefining traditional norms and stereotypes. From digital platforms of the organizations Status Queer, Diálogo Diverso, and Fundación Ecuatoriana Equidad, the ways of expression and construction of gender identity are identified and examined. With the help of content analysis and interviews, accurate information can be obtained on how identity expression and construction has been transformed in the digital age; the use of inclusive language, education and awareness, and the visibility of diverse gender representations and sexual orientations have gained great relevance thanks to the digital platforms analyzed. This research concluded that digital platforms have emerged as significant spaces for the construction and expression of gender identity. With the use of social networks, different gender identities can be expressed in a broad and diverse environment compared to the physical world. It is also recommended that collaboration be generated between digital platforms, educators and support organizations, since they are essential to develop and distribute educational resources that address gender diversity. These resources must be accessible, relevant and designed to attract youth, using multimedia formats that are attractive and easy to understand.